DEVELOPING DIGITAL TEACHING MATERIALS FOR PROSE FICTION APPRECIATION TO FOSTER LEARNING AND ENGAGEMENT - Siti Cholisotul Hamiah; Endah Tri Priyatni; Heri Suwignyo (Jurusan Sastra Indonesia, 2018)
This study is aimed at developing digital teaching materials for Prose FictionAppreciation course to foster students’ learning and engagement. This study employedresearch and development design summarized in 4D steps: Define, Design, Develop,and Disseminate. The results of validation and product testing show that the teachingmaterials are suitable for the learning and able to foster the students’ learning andengagement. The notion of engagement is of great importance to be promoted as itsuggests that the students are active learning subjects.